ANALISIS FAKTOR-FAKTOR PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER ADVENTURE DIKALANGAN MAHASISWA - Ramadina, Tarisya Rizki; Umbara, Taufan (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research is to analyze consumer behavior factors related to students' decisions when purchasing Eiger Adventure products. This research aims to understand consumer behavioral factors towards Eiger Adventure products and determine consumer behavioral factors that partially or simultaneously influence students' purchasing decisions for Eiger Adventure products. This research uses quantitative descriptive methods. The sampling technique was conducted on 385 respondents through questionnaires distributed on social media using purposive sampling. Data analysis consists of descriptive analysis. Validity and Reliability Test Classical Hypothesis Testing Multiple Linear Regression Hypothesis Testing and Coefficient of Determination Test using IBM SPSS software. The research results on cultural factors, social factors, personal factors and psychological factors are classified as very good and have an important influence on partial and simultaneous purchasing decisions. Keywords: Consumer Behavior, Purchasing Decisions, Eiger